LYVIB / Nur Awatif Yashak and Norarifah Ali - Yashak, Nur Awatif; Ali, Norarifah (Faculty of Art and Design, 2021)
Preparedness should be a priority for future pandemic outbreaks. In this pandemic issue our life has totally changed and we have to live in this new normal life. Everyone need to practice a social distance when they go out especially for elderly person because they are at a high risk to be infected by the virus. Through the designer’s research on this pandemic issue, she found out the idea to design a new product to solve this problem. Many elderly people and their children are not afraid of this virus and they do not know how the virus spreads and how dangerous the virus is. After doing the research in depths the designer found out that most of the elderly in Malaysia have a chronic disease like high blood pressure, kidney disease, heart disease and other illnesses. So, after doing a research and distributing the questionnaire analysis, designer decided to create a social distancing tool for elderly person to make them follow the rules which has been set by MOH to keep a distance of 1 meter while in public places or crowded places. The objective of this product is to secure elderly people by maintaining the distance, to avoid elderly people from being in crowded places, to ensure the safety of elderly people from the virus. The concept that designers used for this product is Hi-Tech. The reason why the designer chose this partial style is because nowadays many people like the product that follows the passage of time.